PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN IBU TENTANG PERAWATAN TALI PUSAT DI DESA SIDODADI KABUPATEN LAMPUNG TIMUR TAHUN 2018 - Agiesta Sephya Shobarina; Aat Sriati; Iwan Shalahuddin (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2019)
ABSTRACT Background: Elderly Health problems can lead to decline in elderly body functions and become a factor that improves health problems. As a result, many elderly people come to public health services every day with the same complaints and different complaints.Purpose: to recognize the description of health problems among the elderly at Majalaya public health centers (Puskesmas) West Java-IndonesiaMethods: A descriptive research with documentation study. The object of research is medical records of elderly who went to public health center during the last 1 year from April 2017 until March 2018. The number of samples is 3899 elderly based on elderly visit number gained by total sampling technique. The technique of data collection is through elderly medical records at Majalaya Public Health Centre during the last 1 year. This research uses frequency distribution and proportion analysis.Results: Showed that almost all elderly came independently without being escorted by their families and hypertension was the highest-ranking health problems experienced by elderly (40,9%) others were rheumatoid atritis (14,9%), cough and flu (8.2%) , gastritis (7,9%) and chepalgia (7.6%) , they were the 5th highest health problems experienced by the elderly at Majalaya Public Health center during the last 1 year.Conclusion: Among 22 health problems that are experienced by elderly, hypertension is the most common problem complained by elderly. It is recommended that health care workers optimize services regarding the handling and treatment of chronic health problems among elderly.